Solid Phase Extraction and Flame Atomic Absorption Spectrometry for the Determination of Trace Lead - Yang, Jie; Xue, Jingjiao; Cao, Jingli; Hu, Qiufen; Ning, Ping; Yang, Guangyu (Asian Journal of Chemistry, 2010)
A reliable and rapid method for determination of lead using C18 disc impregnated with 4-hydroxy- 1-naphthal thiorhodanine (HNTR) and flame atomic absorption spectrometry is presented. The influence of aqueous phase pH, type of eluent, flow rates of sample solution and eluent, volume of eluent has been investigated. The method developed for determination of lead is good as seven replicate determinations provides a relative standard deviation (RSD) of 2.5-3.2 %. The selectivity of the proposed method was confirmed from the interference studies. The developed procedure was successfully applied for the determination of lead in tobacco, Chinese herb medicine and water.